State of scientific development issues identity of a minor selfish and violent criminals - Маршуба, М. О. (Problems of legality, 2013)
In a scientific article on the basis of system analysis of concepts such as "self-interested person-but-violent offender", "face a juvenile offender," is its own definition of "person selfish and violent juvenile crime nick." In addition, the scientific article is to review the provisions that determine the identity of the minor issues elaboration selfish and violent criminals at the present stage of development of criminological science.